Metagenomic 18S rDNA reads revealed zonation of eukaryotic communities in the Yongle blue hole - Zhang, Hongxi; Wei, Taoshu; Li, Qingmei; Fu, Liang; Li, Manjie; He, Lisheng; Wang, Yong (Frontiers in Microbiology, 2024)
The Yongle blue hole (YBH), situated in the South China Sea, represents a compelling subject of study in marine microbiology due to its unique redox-layered microbial ecosystems. However, the diversity and ecology of microbial eukaryotes within the YBH remains underexplored. This study endeavors to bridge this gap through the application of the in situ microbial filtration and fixation (ISMIFF) device to collect 0.22-30 μm microbial samples from 21 water layers of YBH. Subsequent extraction of 18S rRNA metagenomic reads of 21 metagenomes and 10 metatranscriptomes facilitated a comprehensive analysis of community structures. Findings revealed a pronounced superiority in the diversity and richness of eukaryotic microorganisms in the oxic zone compared to its suboxic and anoxic counterparts. Notably, Dinophyceae and Maxillopoda emerged as the predominant taxa based on the analysis of the 18S rRNA reads for the V4 and V9 regions, which showed stratification in their relative abundance and suggested their potential role in the thermo-halocline boundaries and oxic-anoxic interface. Specifically, in these eukaryotic microbial communities, Dinophyceae exhibited significant abundance at 20 m (20.01%) and 105 m (26.13%) water depths, while Maxillopoda was prevalent at 40 m (22.84%), 80 m (23.19%), and 100 m (15.42%) depths. A part of these organisms, identified as larvae and protists, were likely attracted by swarming chemosynthetic bacterial prey prevailing at the thermo-halocline boundaries and oxic-anoxic interface. Furthermore, the phylogenetic relationships of the major 18S operational taxonomic units (OTUs) showed a close adjacency to known species, except for three Dinophyceae OTUs. In conclusion, this study provides critical insights into the vertical distribution and transcriptional activity of <30-μm eukaryotic microbes, shedding light on the taxonomic novelty of eukaryotic microorganisms within the semi-enclosed blue holes.